Diffusion of Innovations in the Implementation of Assessments Through Google Forms - Yuono, Yessy Septiani; Huda, Nuril; Sucipto, Sucipto; Restu, Dian Maritra (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
This study employed a qualitative descriptive approach, supported by a structured Likert-scale questionnaire distributed online to 20 tutors at LBB YSY PRIVATE. While quantitative instruments were used for data collection, the primary emphasis was placed on the qualitative interpretation of tutors’ perceptions and experiences regarding digital assessment implementation. The analysis process involved categorizing Likert-scale responses to identify prevailing patterns using descriptive statistics, followed by a thematic analysis to uncover deeper qualitative insights from the identified trends. This combined analytical approach allowed for systematic documentation of response frequencies while preserving the depth and complexity typical of qualitative research. The results provide both measurable patterns and a nuanced understanding of tutors’ experiences with Google Forms, highlighting aspects such as perceived efficiency, challenges encountered, and levels of technology acceptance. This hybrid methodology proved particularly valuable in educational technology research, where both empirical data and experiential insights are crucial for a comprehensive understanding.